2016
DOI: 10.1002/mbo3.375
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal and saprotrophic fungi respond differently to long‐term experimentally increased snow depth in the High Arctic

Abstract: Changing climate is expected to alter precipitation patterns in the Arctic, with consequences for subsurface temperature and moisture conditions, community structure, and nutrient mobilization through microbial belowground processes. Here, we address the effect of increased snow depth on the variation in species richness and community structure of ectomycorrhizal (ECM) and saprotrophic fungi. Soil samples were collected weekly from mid‐July to mid‐September in both control and deep snow plots. Richness of ECM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 77 publications
(87 reference statements)
5
35
1
Order By: Relevance
“…Several studies have experimentally demonstrated that the composition and function of fungal communities shift in response to increased snow accumulation or temperature (Deslippe, Hartmann, Simard, & Mohn, ; Geml et al., , ; Morgado et al., , ; Mundra et al., ; Semenova et al., , ). However, further investigations are needed, since complex interactions may occur with habitat type (Morgado et al., ), changes in N deposition (Lilleskov et al., ), date of snowmelt (Schmidt et al., ), microbial activity in winter (Aanderud, Jones, Schoolmaster, Fierer, & Lennon, ; Buckeridge & Grogan, ; Schimel, Bilbrough, & Welker, ; Semenchuk et al., ), floristic composition or climatic variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have experimentally demonstrated that the composition and function of fungal communities shift in response to increased snow accumulation or temperature (Deslippe, Hartmann, Simard, & Mohn, ; Geml et al., , ; Morgado et al., , ; Mundra et al., ; Semenova et al., , ). However, further investigations are needed, since complex interactions may occur with habitat type (Morgado et al., ), changes in N deposition (Lilleskov et al., ), date of snowmelt (Schmidt et al., ), microbial activity in winter (Aanderud, Jones, Schoolmaster, Fierer, & Lennon, ; Buckeridge & Grogan, ; Schimel, Bilbrough, & Welker, ; Semenchuk et al., ), floristic composition or climatic variability.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have experimentally demonstrated that the composition and function of fungal communities shift in response to increased snow accumulation or temperature (Deslippe, Hartmann, Simard, & Mohn, 2012;Geml et al, 2015Geml et al, , 2016Morgado et al, 2015Morgado et al, , 2016Mundra et al, 2016;Semenova et al, 2015Semenova et al, , 2016.…”
Section: Potential Impacts Of Environmental Changes On Fungal Commumentioning
confidence: 99%
“…While temperate, boreal and arctic soil fungi communities have been examined in detail using environmental high‐throughput sequencing methodologies (e.g., O'Brien et al ., ; Clemmensen et al ., ; Tedersoo et al ., ; Mundra et al ., ), the diversity of soil fungal communities in the tropics is relatively rarely sampled. For example, Tedersoo et al .…”
Section: Introductionmentioning
confidence: 99%
“…While temperate, boreal and arctic soil fungi communities have been examined in detail using environmental high-throughput sequencing methodologies (e.g., O'Brien et al, 2005;Clemmensen et al, 2013;Tedersoo et al, 2014;Mundra et al, 2016), the diversity of soil fungal communities in the tropics is relatively rarely sampled. For example, Tedersoo et al (2014) found the Agaricomycotina to be dominating the fungal communities in their Neotropical forests sites and that Yeasts comprised less than 1% of their operational taxonomic units (OTUs).…”
Section: Introductionmentioning
confidence: 99%
“…While temperate, boreal and arctic soil fungi communities have been examined in detail using environmental high-throughput sequencing methodologies (e.g., Clemmensen et al, 2013;Mundra et al, 2016;O'Brien et al, 2005;Tedersoo et al, 2014), the diversity of soil fungal communities in the tropics is relatively rarely sampled. For example, Tedersoo et al (2014) found the Agaricomycotina to be dominating the fungal communities in their Neotropical forests sites and that Yeasts comprised less than 1% of their operational taxonomic units (OTUs).…”
Section: Introductionmentioning
confidence: 99%